All the taxpayers need to know about the train law - Recalde, Eric R. (Manila, Philippines : Rex Book Store, 2018)
The TRAIN seeks to enhance the progressivity of the tax system through the rationalization of the Philippine internal revenue tax system xxx (and) to provide, as much as possible, an equitable relief to a greater number of taxpayers and their families in order to improve level of disposable income and increase economic activity.